2021
DOI: 10.33448/rsd-v10i7.16226
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade oleoquímica das sementes de gergelim (Sesamum indicum) e girassol (Helianthus annus)

Abstract: Vegetable oils are extremely important for the human organism, being considered a source of energy and of fat-soluble vitamins (A, D, E and K), and fundamental in promoting the taste of food. Sunflower oil is obtained from the seed of the plant Helianthus annuus L., of the Compositae family, standing out for being the fourth oilseed in grain production and the fifth in cultivated area in the world. Another valuable seed used for oil extraction is sesame (Sesamum indicum, L.), which belongs to the Pedaliaceae f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Their chemical analyses of SFO were done using the variables: iodine, peroxide, acidity indexes, and percentage of free fatty acids. Castro et al (2021) also demonstrate that the extraction process, industrial processing, and storage conditions influence the product's quality.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Their chemical analyses of SFO were done using the variables: iodine, peroxide, acidity indexes, and percentage of free fatty acids. Castro et al (2021) also demonstrate that the extraction process, industrial processing, and storage conditions influence the product's quality.…”
Section: Discussionmentioning
confidence: 88%
“…The sunflower oil used in food has a high content of monounsaturated and polyunsaturated fatty acids, especially linoleic and oleic acids (Castro et al, 2021;Rabonato et al, 2017). The present study also observed the same high percentage of components, with the SFO's chromatographic analysis identifying the presence of unsaturated fatty acids (82.20%), primarily linoleic (47.8%), oleic (28.70), and linolenic (3.9%) acids, followed by saturated (12.70%), palmitic (8.8%), and stearic (3.6%) acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Neves et al (2021) when studying physical-chemical characterization of the sunflower produced in cerrado south of Mato Grosso, reported acidity levels of 0.62mg/KOH and Laillou et al (2012), in their research entitled lowquality vegetable oil is the limit for successful vitamin A fortification in Egypt, obtained acidity from 0.45 to 0.90mg/KOH and Castro et al (2021) when evaluating the oil chemical quality of sunflower seeds, they found acidity index of 0.79 g/KOH.…”
Section: Acidity Levelmentioning
confidence: 99%